Is war good or a bad thing: Croatian, Israeli and Palestinian children's attitudes toward war - Kuterovac-Jagodić, Gordana (Array, 2000)
It has been documented that childrens basic attitudes towards social questions such as war and peace are formed during the early school-age period. The aims of the study were threefold: (1) to examine attitudes of Croatian school-age children toward war and peace; (2) to explore relationship between the attitudes and childrens gender, age and amount of experiences with war and violence, and (3) to compare Croatian children's attitudes toward war and peace to the attitudes of Israeli and Palestinian children that were examined by the same scale 18 years earlier. Sample consisted of 230 children aged 11-14 years that attended school in Zagreb, Croatian capital. The attitudes were examined by the Attitude Scale Toward War and Peace (Punamäki, 1987) that was already used on several samples of Middle-East children. Childrens war experiences were examined by the Questionnaire on Childrens Stressful and Traumatic War Experiences (Franc, Kuterovac and Stuvland, 1993). The obtained data indicate that attitudes of Croatian children are negative towards war in general, but are strongly supportive for the particular fight for the freedom of their nation. The results suggest that childrens gender, age and war experiences are related to their attitudes toward war. The comparison of Croatian, Israeli and Palestinian children revealed nationhood influence on attitudes toward war. However, the results indicate that similarity of contemporary Croatian and former Israeli children is greater than both between todays Croatian and former Palestinian children and between Israeli and Palestinian children 18 years ago.